2010
DOI: 10.1007/s11064-010-0361-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of GAD65 and 67 Immunoreactivity in the Lumbar Spinal Cord Between Young Adult and Aged Dogs

Abstract: We investigated distribution and age-related changes in two isoforms of GABA synthesizing enzymes, glutamic acid decarboxylase (GAD) 65 and 67, in the lumbar levels (L(5)-L(6)) of the dog spinal cord. Male German shepherds were used at 1-2 years (young adult dogs) and 10-12 years (aged dogs) of age. GAD65 immunoreaction was observed in neuropil, not in cell bodies, in all laminae of the adult lumbar spinal cord: Many punctate GAD65-immunoreactive structures were shown in all laminae. The density of GAD65 immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 41 publications
0
7
1
Order By: Relevance
“…It was reported that not marked loss of neurons in the aged spinal cords of dog [2122]. In addition, we hardly observed F-J B stained neuron in the both cervical and lumbar region of adult and aged spinal cords.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…It was reported that not marked loss of neurons in the aged spinal cords of dog [2122]. In addition, we hardly observed F-J B stained neuron in the both cervical and lumbar region of adult and aged spinal cords.…”
Section: Discussioncontrasting
confidence: 69%
“…It has reported that microglial activation was increased in the spinal cords without neuronal loss in mice and dogs [2227]. Age related degenerative process in the spinal cord is accompanied by changes in various factors such as neurotransmitters, hormones, oxidative stress, and inflammation [2829303132].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in other organs such as the heart, the amount of caspase-dependent (120-kDa) form of aII-spectrin cleavage is 17% higher in 36-month hearts than in the 6-month hearts of F344XBN rats [2]. Recently, we did not observe any significant changes in the number of NeuN-positive neurons in the gray matter of the spinal cord between adult and aged dogs [27][28][29]. However, it was reported that microtubule-associated protein 2 (MAP2), a cytoskeleton, was age-dependently decreased in the medial prefrontal cortex in the aging model such as senescence-accelerated mouse prone 10 strain and MAP2 immunoreactive and levels were decreased in the spinal cord of the aged dog [12,39].…”
Section: Discussionmentioning
confidence: 67%
“…In both adult and aged groups, we found that the staining pattern and number of NeuN (a marker for neurons) immunoreactive neurons were similar in both groups [27][28][29].…”
Section: Neun Immunoreactivitymentioning
confidence: 73%
See 1 more Smart Citation